Pig slurry composting as a nitrogen source in proso millet crop - Alieze Nascimento da Silva; Claudir José Basso; Dionei Schmidt Muraro; Cícero Ortigara; Edivan Pansera (Pesquisa Agropecuária Tropical, 2016)
With the intensification of pig farming systems, in Brazil, the production of swine waste has increased considerably, leading to water and soil contamination, due to its improper release. Pig slurry composting is an alternative that can be used in order to avoid or reduce negative impacts, especially for producers with physically limited farm areas, or those who intend to increase the number of animals in their production units. This study aimed at evaluating the influence of pig slurry compost doses on the agronomic characteristics and grain yield of proso millet. A randomized blocks design experiment was installed with four replications and five treatments: control without fertilization, control with mineral fertilizer (NPK) and pig slurry compost doses (4.0 Mg ha-1, 8.0 Mg ha-1; 12.0 Mg ha-1). The pig slurry composting increased the dry matter yield, number of grains per plant and grain yield of proso millet, when compared to the control with or without mineral fertilizer. The proso millet yield, at the doses of 8.0 Mg ha-1 and 12.0 Mg ha-1 of pig slurry, was superior than for both the control without fertilization and the control with the recommended mineral fertilizer, with the latter reaching a maximum agronomic efficiency at the dose of 8.0 Mg ha-1.